The Courage of Female Seaweed Farmers - Sukarman Kamuli (AIBPM Publisher, 2019)
In most families, the role of breadwinner always goes to male figure. Females usually take part of supporting a family in domestic circumstances only. This paradigm applies as well in fishing communities. The wives passively wait for the remittances sent home by the men from fishing or cultivating seaweed. Wives of fishermen basically will have equal potential to support their family financially, if they were provided with knowledge and skills as their husbands have especially in cultivating seaweed. Seaweed farming is preferred for them to prioritize household activities still while offering support for the family income. Domestic women are encouraged to participate in the public sector, as a way of fulfilling one target of MDGs (Millennium Development Goals) 2010 in promoting gender equality and women empowerment. The promotion has reached the desired target, as reported by Bappenas (State Ministry for Development Planning) in 2011. The effort of empowering them is divided into five stages, i.e., (1) raising awareness; (2) socialization to grow interest; (3) evaluation; (4) trial (on a smaller scale); and (5) applying selected solutions in the social problem-solving attempt. The informants were female seaweed farmers in Gorontalo Utara regency. The method utilized survey, observation, and interview. The results revealed that the courage of the female in seaweed farming is outstanding, which in turn help improve the household income.